2022
DOI: 10.1039/d2dt01384c
|View full text |Cite
|
Sign up to set email alerts
|

A new broadband near-infrared emitting Mg2Al4Si5O18:Cr3+ phosphor for night-vision imaging

Abstract: Phosphor-converted light-emitting diodes (pc-LEDs) have important applications in security surveillance and food testing, however, developing new broadband near-infrared phosphors remains an important issue. Herein, the high-temperature solid-state reaction method was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…By calculation with eq , the Δ E values of CKSP:1.0Mn 2+ , CKSP:1.0Mn 2+ , 0.02Eu 2+ , and CKSP:1.0Mn 2+ , 0.02Eu 2+ , 0.40Ce 3+ samples are 0.25, 0.22, and 0.21 eV, respectively, as shown in Figure S9d–f. According to a previous study, the decrease in activated energy will increase the probability of nonradiative transitions . In addition, the luminescence intensity of Eu 2+ and Ce 3+ ions decreases because of the increase in temperature, further reducing the energy transfer efficiency among Ce 3+ -Eu 2+ -Mn 2+ .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…By calculation with eq , the Δ E values of CKSP:1.0Mn 2+ , CKSP:1.0Mn 2+ , 0.02Eu 2+ , and CKSP:1.0Mn 2+ , 0.02Eu 2+ , 0.40Ce 3+ samples are 0.25, 0.22, and 0.21 eV, respectively, as shown in Figure S9d–f. According to a previous study, the decrease in activated energy will increase the probability of nonradiative transitions . In addition, the luminescence intensity of Eu 2+ and Ce 3+ ions decreases because of the increase in temperature, further reducing the energy transfer efficiency among Ce 3+ -Eu 2+ -Mn 2+ .…”
Section: Resultsmentioning
confidence: 90%
“…According to a previous study, the decrease in activated energy will increase the probability of nonradiative transitions. 61 In addition, the luminescence intensity of Eu 2+ and Ce 3+ ions decreases because of the increase in temperature, further reducing the energy transfer efficiency among Ce 3+ -Eu 2+ -Mn 2+ . Moreover, multi-ion codoped samples usually have more channels of nonradiative transition.…”
Section: T I Cementioning
confidence: 99%
“…Thus, one of the promising solutions is applying Cr 3+ -substituted phosphors as more effective NIR light sources. The proposed strategy’s potential has been nicely demonstrated in numerous scientific papers ,, where researchers show the potential of these systems by taking digital photographs of samples irradiated with a NIR pc-LED and detected using a NIR camera.…”
Section: Applications Of Nir Pc-leds Based On Cr3+mentioning
confidence: 96%
“…Near-infrared (NIR) spectroscopy in the 700 nm to 1700 nm region of the electromagnetic spectrum has become a research hotspot due to its widespread application in medical diagnostics, night vision, , plant cultivation, , remote sensing, and food freshness analysis. , The historical and universal approach for creating a NIR emission in this window has involved using tungsten lamps that produce a desirable broadband luminescence. However, these sources are extremely energy inefficient, with most energy lost as heat .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that MASO can be used as an excellent matrix for NIR phosphors. 35–37 However, the fluorescence properties of MASO:Cr 3+ in the high and low temperature phases have not been clarified, and the effect of different synthesis temperatures on the properties of phosphors has not been systematically explored.…”
Section: Introductionmentioning
confidence: 99%